PENERAPAN MODEL PEMBELAJARAN TWO STAY TWO STRAY UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS IV UPTD SD NEGERI 62 PAREPARE - Nur Ilmi; Nurul Aziza Hanafi; Andi Fajar Asti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the low speaking skills and learning process of the 4th-grade students at UPTD SD Negeri 62 Parepare. Therefore, the aim of this study is to determine whether the application of the Two Stay Two Stray learning model can improve the learning process and speaking skills of the 4th-grade students at UPTD SD Negeri 62 Parepare. This research uses a qualitative approach with classroom action research (CAR) as the research type. The subjects of this study consisted of 25 participants, including 1 teacher and 24 students of the 4th grade at UPTD SD Negeri 62 Parepare. Data were collected through observation, tests, and documentation. The data analysis techniques used were condensation, presentation, and conclusion drawing. The study was conducted in two cycles. The results show that there was an improvement in both the learning process and the speaking skills of the students. Students became more active in asking questions, more engaged in discussions, more enthusiastic in receiving lessons, able to express opinions and ideas clearly, and more confident in speaking in front of the class. Thus, the application of the Two Stay Two Stray learning model can enhance the learning process and speaking skills of students.